Molecular mechanism of high glucose-induced mitochondrial DNA damage in retinal ganglion cells: High glucose-induces mitochondrial DNA damage in retinal cells - Zhou, Jinzi; Chen, Fenghua; Yan, Aimin; Xia, Xiaobo (Cellular and Molecular Biology, 2024)
Mitochondrial DNA damage in retinal ganglion cells (RGCs) may be closely related to lesions of glaucoma. RGCs were cultured with different concentrations of glucose and grouped into 3 groups, namely normal control (NC) group, Low-Glu group, and High-Glu group. Cell viability was measured with cell counting kit-8, and cell apoptosis was measured using flow cytometry. The DNA damage was measured with comet assay, and the morphological changes of damaged mitochondria in RGCs were observed using TEM. Western blot analyzed the expression of MRE11, RAD50, and NBS1 protein. Cell viability of RGCs in Low-Glu and High-Glu groups were lower than that of NC group in 48 and 96 h. The cell apoptosis in NC group was 4.9%, the Low-Glu group was 12.2% and High-Glu group was 24.4%. The comet imaging showed that NC cells did not have tailings, but the low-Glu and high-Glu group cells had tailings, indicating that the DNA of RGCs had been damaged. TEM, mitochondrial membrane potential, ROS, mitochondrial oxygen consumption, and ATP content detection results showed that RGCs cultured with high glucose occurred mitochondrial morphology changes and dysfunction. MRE11, RAD50, and NBS1 protein expression associated with DNA damage repair pathway in High-Glu group declined compared with Low-Glu group. Mitochondrial DNA damage caused by high glucose will result in apoptosis of retinal ganglion cells in glaucoma.